Regulation of Hedgehog Signaling by miRNAs and Nanoformulations: A Possible Therapeutic Solution for Colorectal Cancer - Javed, Zeeshan; Javed Iqbal, Muhammad; Rasheed, Amna; Sadia, Haleema; Raza, Shahid; Irshad, Asma; Koch, Wojciech; Kukula-Koch, Wirginia; Głowniak-Lipa, Anna; Cho, William C.; Sharifi-Rad, Javad (Frontiers in Oncology, 2021)
Hedgehog (Hh) signaling aberrations trigger differentiation and proliferation in colorectal cancer (CRC). The current approaches to inhibit this vital cellular pathway involve small molecule inhibitors which provoke some serious side effects.. Therefore, it is necessary to look for new therapeutic options. MicroRNAs (miRNAs) are small molecules that modulate expression of different genes and can be utilized as a potential therapeutic option for CRC. Nanoformulations have been implemented in the treatment of plethora of diseases. Owing to their limited cytotoxicity, excessive bioavailability and high specificity nanoparticles NPs can be used as an alternative drug delivery platform for the Hh signaling mediated colorectal cancer. This article reviews the hedgehog signaling and its involvement in CRC with focus on miRNAs and nanoformulations as possible diagnostic/prognostic and therapeutics for the CRC.